Factors predicting the resilience of school re-integrated teenage mothers in Zimbabwe - Taruvinga Muzingili (Cogent Education, 2025)
This study investigated the factors predicting resilience among teenage mothers reintegrated into schools in Zimbabwe. The data were collected from (n = 377) teenage mothers (aged 13–19) who dropped out of school due to pregnancy and were later reintegrated. Data were collected using a structured questionnaire and analyzed through bivariate and multiple linear regression models. Emotional well-being (EW) (β = 0.600, p < 0.01) and coping strategies (β = 0.448, p < 0.01) emerged as the strongest predictors of resilience, followed by institutional support (IS) (β = 0.329, p < 0.01) and community support (CS) (β = 0.246, p < 0.05). Surprisingly, social support (SS) showed a negative relationship with resilience (β = −0.653, p < 0.01), potentially indicating overdependence on external networks. Demographic factors, including years out of school (β = 0.266, p < 0.01), family size (FS) (β = 0.252, p < 0.05) and distance to school (β = −0.141, p < 0.05), moderately influenced resilience. Combined, predictors and demographic factors explained 86.2% of the variance in resilience. The findings highlight the need for interventions that enhance EW, promote self-agency and address structural barriers such as transportation and childcare. These insights inform policies to improve educational outcomes for teenage mothers in Zimbabwe.